1998
DOI: 10.1038/sj.onc.1202211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reactive oxygen species-induced apoptosis and necrosis by caspase 3-like proteases

Abstract: Reactive oxygen species (ROS) and caspases have been implicated as potential mediators of cell death. However, their mechanistic relationship remains to be elucidated. Here we investigated the roles of caspases in apoptosis and necrosis induced by ROS, generated by the mixture of xanthine and xanthine oxidase (X/XO). A low concentration of XO (0.025 U/ml) induced DNA fragmentation with little cellular membrane damage 3 h after treatment, suggesting the induction of apoptosis. The same treatment induced membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 27 publications
14
136
1
Order By: Relevance
“…Alternatively, the di erence between the e cacy of the complex I and II inhibitors may be due to the fact that electrons channeled through complex II produce about four times more superoxide than those channeled through complex I (Forman and Boveris, 1982;Higuchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the di erence between the e cacy of the complex I and II inhibitors may be due to the fact that electrons channeled through complex II produce about four times more superoxide than those channeled through complex I (Forman and Boveris, 1982;Higuchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that Bcl-2 maintains Delta psi by enhancing H + e ux in the presence of agents that induce Delta psi loss and thereby exerts its anti-apoptotic e ects (Shimizu et al, 1998). A question was raised about the requirement of MPT for apoptosis by recent reports, which demonstrated that MPT occurs later than cytochrome c release from mitochondria and caspase activation (Bossy-Wetzel et al, 1998;Higuchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In a previous study, PTD-FNK was demonstrated to reduce ischemic injury to hippocampal CA1 neurons after a transient forebrain ischemia, 18 which involves slow progressive neuronal degeneration, and an apoptotic pathway is suggested to contribute to the ischemic degeneration, to some extent. 19 The enhanced cytoprotective activity of FNK against oxidative stress and a calcium ionophore give rise to the possibility that FNK effectively protects cells from necrosis as well as apoptosis, because oxidative stress [20][21][22] and a disruption of calcium homeostasis [23][24][25] are known to induce necrosis. Carbon tetrachloride (CCl 4 ) has been used to induce necrosis in control experiments for studies on apoptosis [26][27][28][29] and is one of most typical model agents for studying the pathogenesis of liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…33 The combination of X (1 mM) with different concentrations of XO (0.01 or 0.1 units) induced apoptosis in a dose-dependent manner, as determined by annexin V staining (Figure 5b). In contrast, X or XO alone had no effect compared to treatment with vehicle alone.…”
Section: Radiation-induced Depletion Of Reduced Gsh Is Inhibited By Bmentioning
confidence: 99%